The night circus : a novel - Morgenstern, Erin (Vintage Books, 2012)
The circus arrives without warning. It is simply there, when yesterday it was not. Within the black-and-white striped canvas tents is a unique experience full of breathtaking spectacles. This is Le Cirque des Rêves, and it is only open at night. But behind the scenes, a fierce competition is underway, a duel between two young magicians, Celia and Marco, who have been trained since childhood just for this purpose by their instructors. Unbeknownst to them, this is a game in which only one can be left standing, and the circus is merely the stage for a battle to the end of imagination and will. In spite of themselves, Celia and Marco fall in love; and now, though the game must play out, the fates of everyone involved, from the cast of circus performers to the patrons, hang in the balance.